Multi-band second-order bandstop frequency selective structure with controllable band ratios - Abdelmottaleb Omar, Ahmed (2016)
A multi-band second-order bandstop frequency selective structure (FSS) is proposed. The structure is based on controlling the propagating modes in a multi-mode resonator to obtain transmission and reflection zeroes. The band ratios between these multiple bands can be controlled independently. As an example, a tri-band FSS is designed with center frequencies at 10.3, 14.3 and 18.9 GHz and exhibiting fractional bandwidths of 12%, 8% and 9%, respectively. The proposed multi-band FSS has stable filtering performance under various angles of incidence due to its small unit cell size compared to the operating wavelength. The principle of operation is explained along with simulation results.